PENINGKATAN KETERAMPILAN MENULIS CERPEN SISWA SMP NEGERI 3 PERBAUNGAN MELALUI PENERAPAN TEKNIK TRANSFORMASI LAGU - Suyanto, Suyanto; Kartolo, Rahmat (Jurnal Bahastra, 2023)
One of the language skills that are no less important is writing skills. Writing skill is the skill of pouring ideas and thoughts into a written work that can be enjoyed by readers. The aim of this research is to improve short story writing skills through the application of song transformation techniques. This research is included in the type of classroom action research with a population of class X students of SMP Negeri 3 Perbaungan with a sample of 38 students in class X-10. The instruments used in this study were observation, in-depth review, and short story writing skill tests. The analysis technique used is comparative critical analysis. Learning that is carried out by correcting the weaknesses and deficiencies of the learning process carried out by the teacher has a significant impact. This is evidenced by increasing the percentage of student learning completeness from 57.89% to 89.47%, in this case, indicated by the class average score which increased from 64.42 with and standard deviation of 22.95 to 73.11 and a standard deviation of 13.35. If examined in more depth, this increase occurs when the teacher begins to provide feedback in the form of motivation and appreciation to students for overcoming problems in writing, whether caused by a lack of ideas or weaknesses in short story writing techniques.One of the language skills that is no less important is writing skill. Writing skill is the skill of pouring ideas and thoughts into a written work that can be enjoyed by readers. The aim of this research is to improve short story writing skills through the application of song transformation techniques. This research is included in the type of classroom action research with a population of class X students of SMP Negeri 3 Perbaungan with a sample of 38 students in class X-10. The instruments used in this study were observation, in-dept review, and short story writing skill tests. The analysis technique used is comparative critical analysis. Learning that is carried out by correcting the weaknesses and deficiencies of the learning process carried out by the teacher has a significant impact. This is evidenced by increasing the percentage of student learning completeness from 57.89% to 89.47%, in this case, indicated by the class average score which increased from 64.42 and standard deviation of 22.95 to 73.11 and a standard deviation of 13.35. If examined in more depth, this increase occurs when the teacher begins to provide feedback in the form of motivation and appreciation to students for overcoming problems in writing, whether caused by a lack of ideas or weaknesses in short story writing techniques.